Islands of White in a Sea of Red: A Cutaneous Manifestation of Dengue Fever in a Pregnant Woman - Fadlul Azim Fauzi Mansur; Nurul Azmawati Mohamed @ Abd Aziz (USIM Press, 2024)
Vol. 7 No. 3 (2021): Special Issue on Clinical Scenarios In Medicine, A Malaysian Experience (Case Report)